PENGARUH INFORMASI AKUNTANSI BIAYA DAN CSR TERHADAP NILAI PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN - Sabrina, Zafirah Nur; Hidayat, Agus Taufik (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This research aims to determine the effect of cost accounting information proxied by production costs and CSR disclosure on company value as proxied by Tobin's Q. The company that is the object of this research is a food and beverage sub sector manufacturing company listed on the Indonesia Stock Exchange (BEI). The sample in this study consisted of 11 companies using purposive sampling. The analysis model used in this research is a multiple linear regression analysis model. The t-test results show that the production cost variable has a negative effect on company value. Additionally, it is found that CSR disclosure also exhibited a negative correlation with company value, implying that companies engaging in more CSR activities may not necessarily witness a commensurate increase in their valuation. These outcomes contribute valuable insights into the complex dynamics between cost accounting, CSR practices, and corporate value in the context of the examined food and beverage sub sector on the Indonesia Stock Exchange.